2007
DOI: 10.1080/02770900701539723
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination in Adults with Asthma: Safety of an Inactivated Trivalent Influenza Vaccine

Abstract: Despite recommendations in most countries for giving inactivated influenza vaccine to people with asthma, only a minority currently receive it. One reason for low vaccine coverage has been concern that vaccination may induce exacerbations of asthma. In this randomized trial, 291 patients between 18 and 65 years of age received either an inactivated influenza vaccine followed 14 days later by a saline placebo or placebo followed by the vaccine. Each patient received 1 dose of vaccine and 1 dose of placebo. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…A randomized study of IIV3 versus placebo among 262 asthmatic adults noted that vaccination was associated with a decline in peak expiratory flow; however, this effect was no longer significant when adjusted for the presence of concomitant symptomatic cold symptoms (375). A randomized crossover design study of IIV3 versus saline placebo showed no significant difference in the occurrence of asthma exacerbations during the 14 days postvaccination (376).…”
Section: Persons At Higher Risk For Influenza-related Complicationsmentioning
confidence: 99%
“…A randomized study of IIV3 versus placebo among 262 asthmatic adults noted that vaccination was associated with a decline in peak expiratory flow; however, this effect was no longer significant when adjusted for the presence of concomitant symptomatic cold symptoms (375). A randomized crossover design study of IIV3 versus saline placebo showed no significant difference in the occurrence of asthma exacerbations during the 14 days postvaccination (376).…”
Section: Persons At Higher Risk For Influenza-related Complicationsmentioning
confidence: 99%
“…High antibody titers against several antigens (Epstein–Barr, herpes simplex, rubella, measles and parainfluenza viruses, and mismatched blood) have been detected in patients with sarcoidosis 5 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 . In contrast, in the study of Mert et al.…”
Section: Discussionmentioning
confidence: 87%
“…High antibody titers against several antigens (Epstein-Barr, herpes simplex, rubella, measles and parainfluenza viruses, and mismatched blood) have been detected in patients with sarcoidosis. 5,[8][9][10][11][12][13][14][15][16][17][18] In contrast, in the study of Mert et al, 16 none of 16 patients with sarcoidosis developed antibody response to hepatitis B vaccine. In another study, peripheral blood B cells obtained from patients with sarcoidosis produced less immunoglobulin against pokeweed-mitogen compared to normal B cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RCTs, in denen mono-oder bivalente Impfstoffe verwendet (n = 2), verschiedene Influenzaimpfstoffe miteinander verglichen (n = 3), ein atypisches Impfschema angewendet (n = 1) oder in denen Lebendimpfstoffe eingesetzt wurden (n = 3), gingen in die vorliegende Analyse nicht ein. Von den verbleibenden 9 RCTs machten 4 Studien Angaben zu den folgenden von der STIKO a priori festgelegten patientenrelevanten Endpunkten [51,[64][65][66][67] …”
Section: Personen Mit Chronischen Lungenerkrankungenunclassified